Methodological Aspects of Trend Studies and Development of the HBSC Study in the Czech Republic - Sigmund, Erik; Baďura, Petr; Sigmundová, Dagmar; Csémy, Ladislav; Kalman, Michal (Central European journal of public health, 2017)
The aim of the study is to present the theoretical background of trend studies in general, to characterize the international Health Behaviour in School-aged Children (HBSC) study and to describe its methodology and changes of the Czech HBSC study between 1994 and 2014. The first part describes various types of trend research studies including their advantages and disadvantages. The second part summarizes the history of the HBSC study in an international context and particularly in the Czech Republic. The final part presents the basic methodological data from six surveys conducted in the Czech Republic between 1994 and 2014.
Keywords: Cross-Sectional Studies; Health Behavior; Male; longitudinální studie; Health Surveys; Internationality; Adolescent; Česká republika; zdravé chování; Child; trend; teoretické modely; dítě; internacionalita; longitudinal; mužské pohlaví; HBSC; mladiství; výzkumný projekt; Czech Republic; Models, Theoretical; lidé; ženské pohlaví; Research Design; study; Humans; průřezové studie; zdravotnické přehledy; Longitudinal Studies; Female; children; secular